Frequency of Exercise Impacts on Body Weight of Obese Women - Sufahani, S.; Ahmad, S.; Samsi, N.; Seman, N. (Journal of Science and Technology, 2016)
Obesity is weight that is higher than what is considered as healthy weight for a given height. This caused lot of difficulties including health complications. The aim of study is to find the relation between frequency of exercise in a week and total body weight loss in obese women. Total of 40 participants with age 35 years old who obese, selected within 3 neighborhood areas and joined according to their selected program at the same place which is Masjid Kampung Melayu Majideeâ€™s court. There is strong positive correlation with Pearsonâ€™s correlation of 0.8338. Thus, our study confirmed the relation between frequency of exercises in a week and total body weight loss.Â